EFFECT OF PHOTODYNAMIC THERAPY ON SHORT-WAVELENGTH FUNDUS AUTOFLUORESCENCE IN EYES WITH ACUTE CENTRAL SEROUS CHORIORETINOPATHY. Issue 2 (February 2015) - Hagen, Stefan; Ansari-Shahrezaei, Siamak; Smretschnig, Eva; Glittenberg, Carl; Krebs, Ilse; Steiner, Irene; Binder, Susanne
Abstract : Purpose: To evaluate short-wavelength FAF as a parameter of retinal pigment epithelium function in eyes with acute symptomatic central serous chorioretinopathy after indocyanine green angiography-guided verteporfin photodynamic therapy with half-fluence rate. Methods: A retrospective review over a period of 1 year of short-wavelength FAF images of 15 consecutive patients treated with half-fluence rate (25 J/cm 2 ) indocyanine green angiography-guided verteporfin photodynamic therapy due to acute symptomatic central serous chorioretinopathy was performed. Short-wavelength (488 nm) FAF gray values were evaluated with a confocal scanning laser ophthalmoscope at a 350- μ m diameter and a 1, 200- μ m diameter circle centered on the fovea. The change in short-wavelength (488 nm) FAF gray values for the 2 circles was evaluated by calculating the differences of respective values between the first month after treatment and the 3, 6, 9, and 12 months follow-up. Results: Mean differences (95% confidence interval) in short-wavelength (488 nm) FAF gray values of the 350- μ m and 1, 200- μ m diameter circle between the 1-month and the 3-month (n = 15) follow-up were −0.03 (−0.11 to 0.05) ( P = 0.46) and −0.03 (−0.17 to 0.10) ( P = 0.6). Respective differences between the 1 month and the 6 (n = 15), 9 (n = 14), and 12 months (n = 13) of follow-up were −0.03 (−0.11 to 0.05) ( P = 0.42) and −0.04 (−0.16 to 0.08) ( P = 0.5); −0.05 (−0.12 to 0.03) ( P = 0.23) and −0.06 (−0.18 to 0.07) ( P = 0.33); −0.03 (−0.12 to 0.07) ( P = 0.57) and −0.07 (−0.20 to 0.05) ( P = 0.22). Conclusion: Half-fluence rate (25 J/cm 2 ) indocyanine green angiography-guided verteporfin photodynamic therapy did not significantly affect short-wavelength FAF at a 350- μ m diameter and a 1, 200- μ m diameter circle in eyes with resolved acute symptomatic central serous chorioretinopathy throughout 12 months of follow-up. Abstract : No clinically relevant change in short-wavelength fundus autofluorescence (FAF) of 2 circles, 1, 200 μ m and 350 μ m in diameter and centered on the fovea, was observed in patients with resolved acute symptomatic central serous chorioretinopathy after indocyanine green angiography-guided verteporfin photodynamic therapy with half-fluence rate (25 mJ/cm 2 ) over a period of 12 months.